Potresno inženirstvo: Zbirka rešenih primerov - Skrinar, Matjaž; Imamović , Denis (2020)
Earthquake Engineering: Collection of Solved Examples. Earthquake engineering - despite being a relatively young field - is an intensively developing field and is also a very broad area. Therefore, only structural analyzes of buildings are considered in this work, with emphasis on determining the magnitude and distribution of earthquake impact. Just prime controls related exclusively to earthquake engineering are performed, where the detailed controls related to the design of individual materials are omitted. The main reason for such deliberate restriction of the material is the fact that this work is intended for students who meet with these problems for the first time. Therefore, the procedures for solving problems are executed on manual basis i.e. without the use of automated software (except for the calculations of eigenfrequencies and eigenvectors), since the genuine guideline for the preparation of this material was the desire to "persuade" students into a good understanding of the procedures, not just a rather superficial use of computer software for analysis of these problems. This work thus covers the basic content spectrum of the mentioned subject through 10 solved examples, which represent the actual examinations (where some of them also slightly expanded).
Keywords: Earthquake engineering; Seismic impact; Determination of horizontal force; Plane line structures; Distribution of seismic force; Analysis of storeys' displacements